"Pass The Popcorn, Please": Teaching With Documentary Movies In The Introductory Course - Mulderick, Earl (Teaching History: A Journal of Methods, 1996)
One of the challenges in teaching history today is reaching an audience that is not always interested in the subject matter. The problem is often acute in an introductory class where students may be new to college or with returning students whose purpose for enrolling in the survey simply might be to fulfill requirements. James J. Lorence has commented that "student interest in history at two-year campuses is often superficial and sometimes latent." His assessment applies to many students at all colleges and universities, I fear. Lorence urged, however, that teachers of survey classes use their courses to "ignite that spark of inquiry that will lead new generations to value history as a way of learning vital lessons about ourselves, our society, and our world."1 Now that sounds like a clarion-and a noble goal.